Preparation and characterization of (Ba0.85Ca0.15)(Zr0.1Ti0.9)O3 ceramics by a BaTiO3 seed-induced method - Kamnoy M. (2017)
Copyright © 2016 American Scientific Publishers All rights reserved. This research studied the preparation and characterization of (Ba 0.85 Ca 0.15 )(Zr 0.1 Ti 0.9 )O 3 (BCZT) ceramics by a seed-induced method. The seed-induced method serves as a technique using nanocrystals to induce phase formation of a perovskite structure. Firstly, we prepared the BaTiO 3 seeds for the BCZT ceramics by the molten salt method, and we used NaCl:KCl (1:1 by mole) eutectic mixture as the flux and calcined at 750°C. Then, we prepared BCZT ceramics by the solid state method with added content of BT. We calcined the mixed starting powders, including BT seed, at 1200°C for 2 hours and sintered at 1450°C for 4 hours. The results indicated that the BT seed showed a single perovskite phase using a low calcination temperature of 750°C. The average particle size was about 300 nm. The density and average grain size of the BCZT ceramics were 5.41-5.48 g/cm 3 and 7.5 to 15.4 μm, respectively. The highest values for the dielectric constant (ε r ) and piezoelectric constant (d 33 ) were 10876 and 473 pC/N, respectively, for 10 mol% BT-seed-doped BCZT ceramic.